Utilization of Google Apps to Improve the Quality of Services for Organizing the Undergraduate Thesis Defense Registration at the Department of Physics, Universitas Gadjah Mada, Yogyakarta, Indonesia - Sari, Mona; Wahjuni, Trina; Prasetyowati, Rita; Jati, Gandi (Jurnal Manajemen Pendidikan, 2025)
Background The COVID-19 pandemic has significantly impacted education administration services at the Department of Physics, Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Gadjah Mada. Many administrative processes that were previously conducted offline had to transition to online platforms. Purpose This study aims to examine the use of Google Apps in improving the quality of education administration services, specifically in the undergraduate thesis defense registration and graduation process. Design/method/approach The research employs a descriptive qualitative approach, utilizing literature review as the data collection technique. Results The implementation of Google Apps allowed students and administrators to streamline administrative tasks, making processes more effective, efficient, and cost-saving. Google Apps provide features such as online document sharing, group management, task management, calendars, and high-capacity emails. These services enable students to complete the thesis defense registration process more conveniently and help administrators manage their tasks more efficiently. Contribution/value The adoption of Google Apps supports the university’s efforts in successfully implementing digital transformation in education administration. It enhances the efficiency of academic services, reduces costs, and provides a more accessible and flexible system for both students and administrative staff.